Pengaruh Whistleblowing System dan Pengendalian Internal terhadap Pencegahan Fraud - Azhar Huwaiza Fathoni; Jihan Salsabilah; Nera Marinda Machdar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research focuses on the analysis of the Whistleblowing System and Internal Control in relation to Fraud Prevention. Literature review was used as the main method in this research. Agency theory and motivation theory are the theoretical foundations underlying the research. Research findings show that there is a significant correlation between the Whistleblowing System and Internal Control in efforts to minimize fraud in Indonesian organizations. It is hoped that this research can contribute to a deeper understanding for future researchers regarding theories and research results relevant to this topic.